Deciphering the Pathophysiology of Migraine: Understanding Trigeminovascular System Activity and the Importance of the Gut-Brain Axis - Ninoshka Francis (International Journal of Molecular Biotechnological Research, 2024)
Migraine, a prevalent and disabling neurological condition, manifests in distinct phases: premonitory, aura, headache, postdrome, and interictal. Being a primary contributor to adult disability, it presents a substantial economic challenge on a global scale. Even with extensive research spanning centuries, the complete grasp of its root causes continues to evade us. This intricate neurovascular disorder primarily involves local vasodilation of intracranial and extracerebral blood vessels, coupled with simultaneous stimulation of the trigeminal sensory pain pathway, resulting in headaches. Activation of the 'trigeminovascular system' prompts the release of various vasodilators, notably calcitonin gene-related peptide (CGRP), triggering a pain response. Emerging anti-migraine medications target CGRP signaling by either stimulating 5-HT1F receptors on trigeminovascular nerves (inhibiting CGRP release) or directly blocking CGRP or its receptor. Enhanced delineation of pathophysiological processes holds promise for identifying novel therapeutic targets in migraine prevention. This review thoroughly investigates the physiological processes involved in migraines, highlighting the stimulation of the trigeminovascular system and cortical spreading depression (CSD). Furthermore, it explores the impact of the gut-brain axis on the development of migraines. Inflammation within the trigeminovascular system is believed to contribute to the physiological processes of migraines and might be influenced by inflammation and immune modulation in the gastrointestinal (GI) tract, as suggested by recent studies. Similarly, there is compelling evidence suggesting that the gut microbiota plays a significant role in the bidirectional communication between the brain and the gut, and disruptions in this interaction could be associated with neurological conditions like migraines. A significant source of energy for colonic epithelial cells is the short-chain fatty acids (SCFA); acetate, propionate, and butyrate, which are created in the colon by bacterial fermentation of dietary fiber. Researchers utilized the NTG mouse model to explore the correlation between gut microbiota and migraine. Bridging the knowledge gap between our understanding of migraine pathophysiology and the development of enhanced treatments and strategies for patient management is a critical objective in migraine research.
Keywords: CGRP; Migraine; cortical spreading depression; neurological condition; trigeminovascular system